Методы формирования диаграммы направленности в сверхширокополосных антенных решетках для беспроводных точек доступа - Шостко, И. С. (Проблеми телекомунікацій, 2011)
The analysis of relationship between radiation characteristics and the shape of the UWB signal. Introduced dynamically changing the correction parameters of pulses. Presents a method of managing spatial and temporal (spectral) characteristics of the UWB antenna.
Keywords: антенна; сверхширокополосный сигнал; точка доступа; пространственно-временные характеристики; диаграмма направленности